2014
DOI: 10.1007/s13659-014-0013-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Iron-Loaded Veterinary Sarcoma by Artemisia annua

Abstract: Artemisinin, a constituent of Artemisia annua L., is a well-known antimalarial drug. Artemisinin-type drugs also inhibit cancer growth in vitro and in vivo. Herbal extracts of A.annua inhibit the growth of cancer cell lines. Here, we report on the use of capsules containing powder of Herba Artemisiae annuae to treat pet sarcoma. The surgical tumor removal as standard treatment was supplemented by adjuvant therapy with A.annua. One cat and one dog with fibrosarcoma survived 40 and 37 months, respectively, witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 71 publications
0
11
0
3
Order By: Relevance
“…The animals were treated with various doses of 150 mg/day (3 capsules), 450 mg/day (2 capsules), 450 mg/day (3 capsules), and 450 mg/day (2 capsules). All the animals showed complete reduction with no tumor relapse [175].…”
Section: In Vivo Studies Of Anticancer Herbal Medicine: An Overviewmentioning
confidence: 80%
“…The animals were treated with various doses of 150 mg/day (3 capsules), 450 mg/day (2 capsules), 450 mg/day (3 capsules), and 450 mg/day (2 capsules). All the animals showed complete reduction with no tumor relapse [175].…”
Section: In Vivo Studies Of Anticancer Herbal Medicine: An Overviewmentioning
confidence: 80%
“…Scopoletin is a constituent of Artemisia annua L. which is used for malaria treatment and also reveals activity towards cancer, schistosomasis and viral diseases [6,7,8,9,10,11]. We found high amounts of scopoletin in this plant, indicating that artemisinin may not be the only bioactive compound in A. annua [12]. Scopoletin is known for its cytotoxicity towards cancer cells [13,14,15].…”
Section: Introductionmentioning
confidence: 98%
“…An open-label pilot study of patients receiving artesunate for advanced cervical cancer suggested that it was well tolerated and improved symptoms ( Jansen et al, 2011 ). There has been a phase II trial on the activity of artesunate in non-resectable tumours of dogs ( Rutteman et al, 2013 ) and efficacy of extracts of A. annua in 5 veterinary sarcomas ( Breuer and Efferth, 2014 ). This study examines anti-CRC effects and tolerability of artesunate used as monotherapy in a rigorous study design.…”
Section: Introductionmentioning
confidence: 99%